Visual Literacy of Infographic Review in DKV Students’ Works in Bina Nusantara University - Suprayitno, Suprayitno (Bina Nusantara University, 2018)
This research aimed to provide theoretical benefits for students, practitioners of infographics as the enrichment, especially for Desain Komunikasi Visual (DKV - Visual Communication Design) courses and solve the occurring visual problems. Theories related to infographic problems were used to analyze the examples ofthe student's infographic work. Moreover, the qualitative method was used for data collection in the form of literature study, observation, and documentation. The results of this research show that in general the students are less precise in the selection and usage of visual literacy elements, and the hierarchy is not good. Thus, it reduces the clarity and effectiveness of the infographic function. This is the urgency of this study about how to formulate a pattern or formula in making a work that is not only good and beautiful but also is smart, creative, and informative.